2016
DOI: 10.1016/j.exppara.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of Sorghum bicolor extracts, 3-deoxyanthocyanidins, against Toxoplasma gondii

Abstract: We investigated dried red leaf extracts of Sorghum bicolor for activity against Toxoplasma gondii tachyzoites. S. bicolor red leaf extracts were obtained by bioassay-guided fractionation using ethanol and ethyl acetate as solvents. Analysis of the crude and fractionated extracts from S. bicolor using electrospray ionization mass spectrometry (ESI-MS) showed that they contained significant amounts of apigeninidin, luteolinidin, 7-methoxyapigeninidin, 5-methoxyapigeninidin, 5-methoxyluteolinidin, 7-methoxyluteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Based on the elemental composition of the extracts, as determined by ESI-MS analysis, the methanol extract of Chlorophyceae contained higher content of flavonoids/polyphenols, alkaloids (elaeocarpidine and auramine), and artemisic acid with mass numbers of 256.95, 2667.17 and 296.24, respectively, than the n-hexane extract (Figure 2A and 2B). Consistent with our findings in the present study, in our previous study, we have found that Sorghum bicolor red leaf extract fraction that was rich in flavonoids content, had potent in vitro activity against T. gondii at dose levels that were non-toxic to mammalian cells [7].…”
Section: Short Communicationsupporting
confidence: 81%
“…Based on the elemental composition of the extracts, as determined by ESI-MS analysis, the methanol extract of Chlorophyceae contained higher content of flavonoids/polyphenols, alkaloids (elaeocarpidine and auramine), and artemisic acid with mass numbers of 256.95, 2667.17 and 296.24, respectively, than the n-hexane extract (Figure 2A and 2B). Consistent with our findings in the present study, in our previous study, we have found that Sorghum bicolor red leaf extract fraction that was rich in flavonoids content, had potent in vitro activity against T. gondii at dose levels that were non-toxic to mammalian cells [7].…”
Section: Short Communicationsupporting
confidence: 81%
“…The absorbances were read at 490 nm using Synergy Mx BioTek (Vermont, USA) microplate reader with Gen 5 software. T. gondii inhibition activity was expressed as (absorbance of the compounds untreated wells (control) − absorbance of compounds treated/absorbance of compounds untreated) × 100% . Selectivity index of anti‐ T. gondii activity was expressed as [SI = inhibitory concentration required to reduce T‐gondii ‐infected HFF cells growth by 50% (IC 50 )/inhibitory concentration required to inhibit the T. gondii ‐induced cytopathic effect by 50% (IC 50 p)] .…”
Section: Methodsmentioning
confidence: 99%
“…T. gondii inhibition activity was expressed as (absorbance of the compounds untreated wells (control) − absorbance of compounds treated/ absorbance of compounds untreated) × 100%. [27] Selectivity index of anti-T. gondii activity was expressed as [SI = inhibitory concentration required to reduce T-gondii-infected HFF cells growth by 50% (IC 50 )/inhibitory concentration required to inhibit the T. gondii-induced cytopathic effect by 50% (IC 50 p)]. [36][37][38] A cytopathic effect (CPE) is defined as the structural changes that occurred in the HFF cell caused by T. gondii infection.…”
Section: Anti-toxoplasma Gondii and T Gondiiinfected Cytotoxicity mentioning
confidence: 99%
See 2 more Smart Citations